2011
DOI: 10.1111/j.1464-410x.2011.10688.x
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis – medical therapies

Abstract: What ' s known on the subject? and What does the study add? The medical management of urolithiasis is complex. There are many papers written on the topic and many confl icting views. It can be diffi cult for physicians to interpret these data and have a stepwise approach to the medical treatment of stones.Thus this study provides a framework and a review of the literature to allow physicians to practise evidence-based medicine when medically managing urolithiasis. SUMMARYThis review paper provides a summary of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 35 publications
(32 reference statements)
0
20
0
13
Order By: Relevance
“…Being a xanthine oxidase inhibitor it inhibits uric acid production from hypoxanthine and xanthine thus reducing urate levels in urine, which again turns out to be inhibitory for nucleation of calcium oxalate [65][66][67] . Febuxostat is also a xanthine oxidase inhibitor like allopurinol but has been found to be more efficacious in reducing urinary urate levels as compared to allopurinol [21] .…”
Section: Treatment Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a xanthine oxidase inhibitor it inhibits uric acid production from hypoxanthine and xanthine thus reducing urate levels in urine, which again turns out to be inhibitory for nucleation of calcium oxalate [65][66][67] . Febuxostat is also a xanthine oxidase inhibitor like allopurinol but has been found to be more efficacious in reducing urinary urate levels as compared to allopurinol [21] .…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…Potassium citrate also tends to inhibit uric acid stone formation owing to its alkalinizing effect on urine [67][68][69] . Unlike sodium citrate and sodium bicarbonate, it does not tend to raise sodium load, which is known to increase calcium excretion and produce citrate reduction in urine and is therefore preferred over them [66] . But, it does possess tendency for producing gastrointestinal upset [69] .…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…g) Alpha mercaptopropionylglycine (or tiopronin) is a better tolerated alternative to D-penicillamine, but its efficacy and availability is very less as compared to D-penicillamine [36].…”
Section: Treatment Of Nephrolithiasismentioning
confidence: 99%
“…Thiazide diuretics (hydrochlorothiazide) and allopurinol (in patients with idiopathic CaOx stones in hyperuricosuria) are also being used in the management of CaOx stone disease [8]. However, it is also reported that the risk of recurrence is 40% at 5 years and 75% at 20 years after passage of a first stone [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, thiazides decrease urinary calcium excretion but may lead to hypokalemia which in turn cause hypocitraturia and promote stone formation. Similarly, sodium bicarbonate therapy may precipitate CaOx (due to sodium overload) or CaP stone (due to alkaline pH) [8]. This implies that there is a greater need to develop more effective drugs for treating stone disease with fewer or no complications.…”
Section: Introductionmentioning
confidence: 99%